The Effectiveness of Problem-Based Learning in Improving Students' Digital Tabayyun Attitudes: Evidence from Islamic Religious Education Classrooms - Inas Dhia Fauziah; Ela Nurlela; Hikmal Alfiyansyah; Rahayu Kariadinata; Elis Ratna Wulan (IQRO: Journal of Islamic Education, 2026)
The rapid development of digital technology makes it easier to access and share information. However, this also brings various problems, such as the spread of hoaxes, cyberbullying, and online gossip, which often involve teenage students. Therefore, cultivating a digital tabayyun attitude needs to be instilled through Islamic Religious Education (PAI) lessons. This study aims to determine the effectiveness of the Problem-Based Learning (PBL) method in improving the digital tabayyun attitude of seventh-grade students. The study uses a quantitative approach and an experimental method, employing a One-Group Pretest-Posttest Design. Data were collected through a pre-test, implementation of PAI learning using the PBL method, and a post-test administered with a digital tabayyun attitude scale instrument. The results showed that the average digital tabayyun attitude score of students increased from 76.91 in the pre-test to 84.00 in the post-test. The paired sample t-test results showed a significance value of < 0.001, indicating a significant difference between the conditions before and after applying the PBL method. Meanwhile, the N-Gain test results had an average of 29.78%, which falls into the low category. These findings suggest that the Problem Based Learning method can have a positive and significant impact on improving students' digital tabayyun attitudes, even though the level of effectiveness is still considered low. Therefore, a more continuous implementation is needed so that the development of the digital tabayyun character can grow optimally.